An Analysis of Writing Assignments Through The Critical Thinking Skills in The Sixth Semester of English Department UIN Sjech M. Djamil Djambek Bukittinggi - Bagus Purnomo; Elsi Amiza; Irwandi Nashir; Widya Syafitri (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The purpose of the research was to find out the implementation of the indicators of critical thinking skills in the writing assignments of sixth-semester students in the English department. This analysis involved an in-depth understanding of writing structure, language choices, and students' ability to formulate arguments critically. The research proved useful for increasing knowledge about pedagogical writing and providing an in-depth analysis of students' writing assignments. This research was a quantitative descriptive analysis method research. The population of this research were all of the students in the Sixth semester of English Department UIN Sjech M. Djamil Djambek Bukittinggi year 2022/2023. According to the findings of the study, students showed inadequate critical thinking skills while creating 17 specific sub-indicators with scores below of 50%. It was found that students encountered difficulties when writing a thesis assignment. It means that the majority of students were unable to organize thoughts into thesis writing assignments.